Selective Endothelin-B Receptor Stimulation Increases Vascular Endothelial Growth Factor in the Rat Brain during Postnatal Development - Leonard, M. G.; Prazad, P.; Puppala, B.; Gulati, A. (Drug Research, 2015)
Endothelin, vascular endothelial growth factor and nerve growth factor play important roles in development of the central nervous system. ETB receptors have been shown to promote neurovascular remodeling in the adult ischemic brain through an increase in VEGF and NGF. It is possible that ETB receptors may be involved in postnatal development of the brain through VEGF and NGF. In the present study, the brains of male rat pups on postnatal days 1, 7, 14 and 28 were analyzed for expression of ETB receptors, VEGF and NGF. In order to determine the effect of ETB receptor stimulation, a separate group of pups were administered saline or ETB receptor agonist, IRL-1620, on day 21, and their brains were analyzed on day 28. The intensity of ETB receptor and VEGF staining in the vasculature as well as the number of blood vessels of normal pups increased with age and was significantly higher on postnatal day 14 compared to day 1 and day 7. In contrast, both ETB and NGF staining intensity in the cortex and subventricular zones decreased (P<0.01) at postnatal day 14 compared to earlier time points. Stimulation of ETB receptors resulted in a significant increase in VEGF and ETB intensity both in the vasculature and the brain (P<0.05), however, IRL-1620 did not produce any change in NGF expression. Results indicate that ETB receptors appear to play a role in the development of the CNS and selective stimulation of ETB receptors enhances VEGF but not NGF in the postnatal rat brain.
Keywords: endothelin B receptor; vascular endothelial growth factor; nerve growth factor; ontogeny; postnatal development; central nervous system